Treatment of Rural India in the Short Stories of Manoj Das: The Role of Nature in Manoj Das's Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A writer deals with his backdrop and humans around him in his literary work. Manoj Das, who has been compared with O’Henry by many scholars, is undoubtedly a very distinguished writer of India in English. He is a bilingual writer as he writes in Oriya as well as English Manoj Das’s literary works which are basically set in rural villages not only depict the community life as a whole but the nature as significant force. His works show his observation of nature. Nature plays crucial role sometimes in the stories of Das. It has been employed skill fully by the writer. Nature and human beings are interconnected with each other. It affects the life of humans sometimes positively. This is the force that offers solace, solitude and what not. European Romantic poets also used nature as a significant motif in their poetry. Even as Wordsworth says, ‘It is “a friend, teacher and guide” for us. The present paper is an attempt to highlight the use of nature in the works, particularly in short stories of Manoj Das. It is to discuss here the role of nature in Das’ stories.